Beginning .NET Game Programming in VB.NET - Weller, David (Apress, 2012)
BACK A FEW YEARS AGO I HAD AN IDEA. What if I could make the power of the DirectX API available to the developers who were going to be using the new set of languages and common language runtime that Microsoft was developing? The idea was intriguing, and opening up a larger portion of the world to DirectX was a goal I was only happy to endorse. Besides, what developer doesn’t want to write games? It seems that at least once a week I am answering questions directly regarding the performance of managed code, and Managed DirectX in particular. One of the more common questions I hear is some paraphrase of “Is it as fast as unmanaged code?”